Contemporary Issues in Evangelism and Mission: perspectives and contributions from the Uniting Church in Australia - Hill, Graham Joseph (Uniting Church studies, 2025)
This article discusses the critical contemporary issues surrounding evangelism and mission, addressing various theological, historical, scriptural, and contextual challenges. It engages with important debates, such as the implications of the missio Dei, the legacies of colonialism on mission practices, and the ethical dimensions of evangelism within a secular, multicultural, and multireligious society. A central focus is placed on the Uniting Church in Australia (UCA), analysing its distinctive theological insights, historical engagement with mission, missiological shifts, and contextual strategies. The paper examines UCA’s unique contributions and argues that its approach offers valuable perspectives for global discussions on evangelism and mission, particularly through its commitment to reconciliation and social justice. Additionally, UCA’s emphasis on contextualised gospel proclamation and embodiment showcases its innovative responses to modern challenges and its resonance with eight themes emerging in world Christianity. This study highlights UCA’s potential to shape the future trajectory of intercultural mission theology and practices, emphasising the importance of adapting evangelistic and missional efforts in a pluralistic world.